Evaluation of the Protonation Energy of Molecules using Conceptual Density Functional Theoretical Reactivity Descriptors - Rajak, Sandip K.; Islam, Nazmul; Ghosh, Dulal C. (Current Physical Chemistry, 2017)
Objective: In this work we have suggested the model for the evaluation of the proton affinity, PA of molecules and also calculated theoretical PA of some molecules using some CDFT descriptors. Method: A validity test of the model is performed by comparing the protonation energies of as many as 45 molecules computed using the model proposed in this work vis-is their corresponding experimental counterparts. Conclusion: The close agreement between the theoretically evaluated and experimentally determined PA's suggests that this modeling and the developed model for computing PA of molecules is efficacious and the hypothesis is scientifically acceptable.
Keywords: proton affinity